Direct imaging searches for substellar companions to nearby stars - Janson, Markus (2008)
Ever since the first detections of extrasolar planet candidates in the early 1990s, our knowledge of such objects has drastically increased, and exoplanet science today constitutes a major branch of astrophysics, with a few hundred individual detections. Our physical understanding is however limited by the fact that the planets are generally only detected indirectly, with just a few constraints on its orbital and physical parameters. Direct imaging of exoplanets, where the planet can be spatially resolved from the star, opens up for a much broader understanding of these objects, with the opportunity to study their spectral characteristics. Alternatively, eclipse spectroscopy, where the planetary signal can be temporally resolved in systems where the orbital plane of the planet happens to align with the line of sight of an observer, can be used for the same purpose. In this thesis, we study various approaches for direct imaging and spectroscopy of exoplanets from the ground, using combinations of adaptive optics and differential methods, in particular spectral and angular differential imaging. The possibility of using an external occulter for the purpose of decreasing the star-planet contrast is studied. We also investigate the possibility to calibrate theoretical mass-luminosity relationships in order to improve detection predictions and the interpretations of null-detection surveys. Scientific results include an improved age range of the AB Dor system thanks to the spatial distinguishing of AB Dor B as a close binary, and the best constrained upper limit to the H-band brightness of any known exoplanet ever achieved, from a deep imaging search for Eps Eri b.
Keywords: Hochschulschrift; Extrasolarer Planet